Tratamiento de la sonrisa gingival con la toxina botulínica tipo A: Caso clínico - Nunes, Levy [UNESP]; Peixoto Ferrão Junior, José; Feres Teixeira, Stephanie A.; Lobo Leandro, Luiz Fernando; García Guevara, Henry Arturo (Inspira Network Group, 2015)
Botulinum toxin has recently been reported in the literature as a treatment option for the correction of the gummy smile. This case report describes the experience of the authors in a case of gingival smile associated with 4. mm of gingival exposure and hyper mobility of the elevator muscle of the upper lip treated with the use of botulinum toxin. Regular checks and assessments of the gingival exposure were performed monthly after the application. Treatment with botulinum toxin type A can be considered as a possible alternative of treatment in this type of cases.
Treatment of gingival smile with botulinum toxin type A: A case report
Keywords: Botulinum toxin type A; Gummy smile; Muscle hyperactivity; Treatment